Vector fields of flapping and gliding swifts - Henningsson, Per; Hedenström, Anders; Bomphrey, Richard J. (Dryad Digital Repository, 2014)
Flow measurements behind swifts (Apus apus) in flapping and gliding flight in the Lund University wind tunnel. The data are in the form of vector fields in DaVis VC7-format. The zipped file contains two folders, one holding all the sequences from the flapping flight experiments and one all the sequences from the gliding flight experiments. Each of these folders contains sub-folders with names corresponding to the flight speed examined during measurements. Inside these subfolders sequences are located and the names of each of them show time and date of acquisition and the major processing steps performed in DaVis. Only sections within these sequences corresponding to steady flight where the complete semi wake span is present were used for analysis.